Bullying Victimization and Life Satisfaction Among Rural Left-Behind Children in China: A Cross-Sectional Study - Yide Yang; Chanjuan Zheng; Ming Xie; Shuqian Yuan; Yuan Zeng; Meiling Zhou; Shuzhen Huang; Yulian Zhu; Xiangli Ye; Zhiyong Zou; Ying Wang; Julien Steven Baker (Frontiers Media S.A., 2021)
Objectives: This study aimed to evaluate the associations between bullying victimization and life satisfaction in primary school children and also investigate the interactive effects of left-behind status and bullying victimization on life satisfaction.Materials and Methods: Bullying victimization was measured using the Chinese version of the revised Olweus Bully/Victim Questionnaire. Life satisfaction was assessed using the Multidimensional Students' Life Satisfaction Scale (MSLSS). Life satisfaction is composed of five domains, namely, family, school, friends, environment, and self-satisfaction. Left-behind status of rural children was defined as one or both their parents migrating to working in cities. The data were analyzed using Mann-Whitney U tests, Chi-square tests, and multivariate linear and logistic regression analyses.Results: A total of 810 primary school children were involved, of which 8.5% reported bullying victimization, and 44.3% were left-behind children (LBC). We found that bullying victimization was negatively associated with all domains of life satisfaction (all p < 0.05). With further left-behind status-stratified analysis, we found that negative association between bullying victimization and friend satisfaction was more profound in the LBC group than in the non-LBC group [b(SE)= −0.133 (0.03) vs. −0.061 (0.026) for LBC and non-LBC, respectively, p < 0.05]. When further interaction analysis was conducted, we identified interaction effects between left-behind status and bullying victimization on friend satisfaction (pinteraction = 0.048). Similar interaction effect between bullying victimization and left-behind status on school satisfaction was also found (pinteraction = 0.004).Conclusions: Bullying victimization was associated with low life satisfaction (including lower family, friends, school, self, and environment satisfaction). There were significant interactions between left-behind status and bullying victimization on friend satisfaction, as well as school satisfaction. Left-behind status of children may exaggerate the impact of bullying victimization on friends/school satisfaction rating.